2021
DOI: 10.1073/pnas.2005759118
|View full text |Cite
|
Sign up to set email alerts
|

Network motifs involving both competition and facilitation predict biodiversity in alpine plant communities

Abstract: Biological diversity depends on multiple, cooccurring ecological interactions. However, most studies focus on one interaction type at a time, leaving community ecologists unsure of how positive and negative associations among species combine to influence biodiversity patterns. Using surveys of plant populations in alpine communities worldwide, we explore patterns of positive and negative associations among triads of species (modules) and their relationship to local biodiversity. Three modules, each incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 50 publications
2
51
0
Order By: Relevance
“…Our study emphasises the raising awareness of considering multiple interaction types simultaneously (e.g. antagonistic and mutualistic) to deepen our understanding of complex biodiversity patterns (Losapio et al ., 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Our study emphasises the raising awareness of considering multiple interaction types simultaneously (e.g. antagonistic and mutualistic) to deepen our understanding of complex biodiversity patterns (Losapio et al ., 2021).…”
Section: Discussionmentioning
confidence: 94%
“…A study in an alpine plant community reports that facilitative and neutral pollinator-mediated interactions among plants prevailed over competition ( Tur et al, 2016 ). Additionally, recent studies have reported that the interplay between competition and facilitation affects local population persistence ( Losapio et al, 2021 ). Such facilitative interactions might affect the coexistence of closely related species.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how biotic interaction affects species composition and distribution is a major ongoing challenge in community ecology. Among biotic interactions, competition is the most important and well-studied interaction ( Goldberg & Barton, 1992 ) although facilitation plays a major role in supporting biodiversity and shaping community structure ( Losapio et al, 2021 ). A common hypothesis related to the role of competition in community assembly, termed the competition-relatedness hypothesis (CRH; Cahill et al, 2008 ), states that closely related species compete more intensely than distantly related species, which hypothetically limits the ability of closely related species to coexist ( Webb et al, 2002 ; Slingsby & Verboom, 2006 ; Prinzing et al, 2008 ; reviewed by Mayfield & Levine, 2010 ; HilleRisLambers et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…By considering the classical analysis on community assembly [41] we have been able to compare those results with our synthetic invasion mechanism. Future work should consider several extensions and more general assumptions, such as relaxing the symmetry constraints on the interaction matrix or the introduction of mutualistic effects, which are known to be relevant in microbial soil communities [43, 44]). Similarly, resource-consumer models would be also useful to test the role played by the engineered strain on available resources.…”
Section: Discussionmentioning
confidence: 99%